2004
DOI: 10.1627/jpi.47.377
|View full text |Cite
|
Sign up to set email alerts
|

Storage and Supply of Pure Hydrogen Mediated by the Redox of Iron Oxides

Abstract: Methods for the storage and supply of pure H2 are proposed based on the reduction of iron oxide with H2 (Fe3O4 + 4H2 3Fe + 4H2O) followed by the oxidation of the iron metal with H2O (3Fe + 4H2O Fe3O4 + 4H2). In addition, production of pure H2 from CH4 is proposed based on the reduction of iron oxides with CH4 (Fe3O4 + CH4 3Fe + CO2 + 2H2O) and the subsequent oxidation of iron metal with H2O (3Fe + 4H2O Fe3O4 + 4H2). Iron oxides without other metal elements were deactivated quickly during these redox cycles due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Otsuka et al [17,32] [19,33]. Figure 18 shows the TPO profiles of reduced NiOCr 2 O 3 -MgO with 4.5 mmol of CH 4 over 4.0 mmol of NiO at 700°C using different oxidants.…”
Section: Tpr On Nio-cr 2 O 3 -Mgo and Tpo After Reductionmentioning
confidence: 99%
“…Otsuka et al [17,32] [19,33]. Figure 18 shows the TPO profiles of reduced NiOCr 2 O 3 -MgO with 4.5 mmol of CH 4 over 4.0 mmol of NiO at 700°C using different oxidants.…”
Section: Tpr On Nio-cr 2 O 3 -Mgo and Tpo After Reductionmentioning
confidence: 99%
“…500 °C is required to split water when compared to a temperature of 420 °C as required by iron oxide modified with Mo [22]. In addition, no oxidation of methane was observed when the temperature was lower than 700 °C [26]. It was proposed that the main role of Cr and Mo dopants was to partially transform the iron oxide into the ferrite structure (MxFe3-xO4, M = Mo and Cr) [22,26] and therefore inhabited the agglomeration of neighbouring particles.…”
Section: Effects Of Metal Addition To Oxide Carriersmentioning
confidence: 99%
“…The role of Rh was to decrease the onset temperature for the water splitting reaction. A XANES/EXAFS study on Rh-Cr-added iron oxide revealed that Rh was also able to form Rh-Fe alloy upon reductions [26]. However, Rh segregated in the alloy structure when it contacted steam and thus accelerated the sintering of iron oxide.…”
Section: Effects Of Metal Addition To Oxide Carriersmentioning
confidence: 99%
“…Previous studies on hydrogen storage by using the chemical looping redox of iron oxide indicated that pure iron oxide could quickly lose reactivity due to agglomeration in the first few redox cycles and the sintering of particles at high operating temperatures. For the commercialization of this technology, it is necessary to modify the iron oxide so that it can be used in repeated redox cycles with high recyclability and stability.…”
Section: Introductionmentioning
confidence: 99%